Functional 3D Structure Analysis of Quasispecies Variants of Hepatitis B Virus Surface and Core Protein in Advanced Liver Disease and Chronic HBV Infection Patients in Indonesia: In Silico - Samuel Johanes Aldrian Mahulette; Adhisa Fathirisari Putri; Azki Afidati Putri Anfa; Yoshihiko Yano; Jajar Setiawan; Putri, Wahyu Aristyaning (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2024)
Hepatitis B Virus (HBV) is an endemic virus and belongs to Hepadnaviridae family. This virus can result in variations of quasispecies due to its high rate of mutation. A quasispecies variant is a small population and develops as a result of mutation and can become a wild-type population. This research aims to study and carry out 3D modeling on 12 in-house full sequence HBV genome isolates from Indonesia and obtain predictive visualization data to become a reference for further research leading to the production of anti-virals and natural treatments for HBV. 12 in-house full HBV genome sequences obtained from previous research were used to carry out 3D modeling and structural analysis of the surface protein, core protein, and polymerase protein. Analysis was carried out in silico using programs available online. Phylogenetic analysis was carried out using MEGA11, translation of nucleotides into protein sequences using the ExPAsy Translate portal, physiochemical analysis using ProtParam portal, and functional domain testing using the MOTIF tool from GenomeNet. Then 3D modelling using Phyre2 and SWISS-MODEL. The major mutation of the S protein occurs in L21S and mutations in the C protein mainly occur in P79Q and S87G. The model for S Protein from homology structure prediction is not reliable thus it still needs more templates from experimental techniques. While C Protein structure prediction can provide information for further research in alternative natural antiviral treatment.